Effect of NAM-1 genes on the protein content in grain and productivity indices in common wheat lines with foreign genetic material introgressions in the conditions of Belarus - O. A. Orlovskaya; S. I. Vakula; K. K. Yatsevich; L. V. Khotyleva; A. V. Kilchevsky (Вавиловский журнал генетики и селекции)
Modern varieties of common wheat (Triticum aestivum L.) bred mainly for high productivity are often of low grain quality. The identification of NAM-1 alleles associated with high grain protein content in wheat relatives has enhanced the significance of distant hybridization for the nutritional value of T. aestivum L. grain. In this work we aimed to study the allelic polymorphism of the NAM-A1 and NAM-B1 genes in wheat introgression lines and their parental forms and evaluate the effects of various NAM-1 variants on the grain protein content and productivity traits in the field conditions of Belarus. We studied parental varieties of spring common wheat, the accessions of tetraploid and hexaploid species of the genus Triticum and 22 introgression lines obtained using them (2017–2021 vegetation periods). Full-length NAM-A1 nucleotide sequences of T. dicoccoides k-5199, T. dicoccum k-45926, T. kiharae, and T. spelta k-1731 accessions were established and registered with the international molecular database GenBank. Six combinations of NAM-A1/B1 alleles were identified in the accessions studied and their frequency of occurrence varied from 40 to 3 %. The cumulative contribution of NAM-A1 and NAM-B1 genes to the variability of economically important wheat traits ranged from 8–10 % (grain weight per plant and thousand kernel weight) to up to 72 % (grain protein content). For most of the traits studied, the proportion of variability determined by weather conditions was small (1.57–18.48 %). It was shown that, regardless of weather conditions, the presence of a functional NAM-B1 allele ensures a high level of grain protein content; at the same time, it does not significantly decrease thousand kernel weight. The genotypes combining the NAM-A1d haplotype and a functional NAM-B1 allele demonstrated high levels of productivity and grain protein content. The results obtained demonstrate the effective introgression of a functional NAM-В1 allele of related species increasing the nutritional value of common wheat.